PERILAKU MEROKOK DAN PENGALAMAN REGULASI Dl BERBAGAI NEGARA - Muhadjir Darwin (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2007)
This paper elaborates smoking behavior and its implication to health as well as household welfare. The controversy of this behavior and its implication is explored: cigarette is demanding goods for many people, particularly men; cigarette industries also contribute a lot to job opportunities, household income, and government revenues, but the health consequences of smoking behavior exceed the benefits. In addition, most smokers in this country spend their limited income more for tobacco than for education and health, and hence affects negatively to their welfare. This paper than explores state regulations applied in many parts of the world since 16th centuries, and efforts to regulate smoking behavior in Indonesia, and their effectiveness to protect people from smoke hazards.